A History of the Founding and Early Years of AFEE. Issue 3 (3rd July 2017) - Cavalieri, Marco; Almeida, Felipe
Abstract: During the late 1950s, institutionalists started organizing themselves amid the decline of institutional economics, leading to the 1965 founding of the Association for Evolutionary Economics (AFEE). We analyze the history of the movement to found AFEE and its early years. We use archival evidence, much of it previously unpublished, to provide a detailed history of these early years. We also present an account of AFEE that highlights the role of different interpretations of institutional economics in building the association. In addition, we provide a brief history of the early years of the Journal of Economic Issues (JEI).